Joint coordination during quiet stance: effects of vision - Krishnamoorthy, Vijaya; Yang, Jeng-Feng; Scholz, John P. (Experimental brain research, 2005)
Stabilization of the center of mass (CM) is an important goal of the postural control system. Coordination of several joints along the human "pendulum" is required to achieve this goal. We studied the coordination among body segments with respect to horizontal CM stabilization during a quiet stance task and the effects of vision on CM stability. Subjects were asked to stand quietly on a narrow wooden block supporting only the mid-foot, with either open (EO) or closed (EC) eyes on separate trials. Instant equilibrium points (IEPs) in the center of pressure (CP) trajectory were determined when the horizontal component of the ground reaction force was zero and the CP data were decomposed into their rambling and trembling components. The joint angle, CM and CP data were divided into short cycles (time-normalized to 100 data points) or longer segments (time-normalized to 1000 data points) of equal length beginning and ending in an IEP. Motor abundance with respect to patterns of joint coordination was evaluated using the uncontrolled manifold (UCM) approach. Here, a UCM is a subspace spanning all joint combinations resulting in a given CM position. All combinations of joint angles that lie within this subspace are equivalent with respect to that CM position while joint angle combinations lying in a subspace orthogonal to the UCM lead to deviation from that CM position. UCM analysis was performed on data organized either across time within longer segments or at each point in time across multiple segments or across multiple cycles. Regardless of method of analysis, most of the variance in joint space was constrained to be within the UCM, preserving the mean CM position in both the EO and EC conditions. Joint configuration variance was significantly higher in the EC than in the EO condition although this increase occurred primarily within the UCM rather than in the orthogonal subspace that would have led to variation of the CM position. These results demonstrate the ability of the control system to selectively "channel" motor variability into directions in joint space that stabilize the CM position. This effect was enhanced when the task was made more challenging in the absence of vision. There was also a significant relationship between joint variance that led to a change in the CM position and, in particular, the rambling component of the CP path, lending some support to the idea that the CNS prescribes a certain stable trajectory of the CP during quiet stance that leads to a small controlled movement of the CM.